Defensive Urbanism in Modern Conflicts: The Case of Ukraine - Rudakova, Bohdana; Tryhub, Ruslana (Academic journal Industrial Machine Building Civil Engineering, 2025)
This paper examines the influence of dense urban development on modern military conflicts, with a focus on Ukraine. The research highlights how urban form dictates the dynamics of combat operations, restricts troop mobility, and shapes tactical decisions. Historical models of fortified cities are considered, as well as contemporary examples, including Israel’s urban planning paradigm. The paper argues that Ukraine must adapt its state-building standards to incorporate defensive urbanism and resilient infrastructure. Recommendations for integrating urban planning with defense strategies are provided.